Cartographie prospective d’évolution du trait de côte et des risques de submersion dans le contexte du changement climatique : une méthode appliquée au littoral du nord de la France - Arnaud Héquette; Marie-Hélène Ruz; Olivier Cohen; François G. Schmitt (VertigO)
Because climate change will likely have major impacts in low-lying coastal areas, our ability for evaluating predictable consequences of coastal hazards in the future already represents a key issue in coastal risk reduction. This paper presents examples of the application of a method aimed at assessing the future position of the shoreline and at mapping areas that will be at risk of flooding by 2065 with future sea-level rise at two coastal localities of northern France where properties are already threatened by erosion or flooding. Our results show that erosion is the main coastal hazard at one of the two study sites where a large part of a housing estate may disappear by 2065 if no action is taken for limiting coastal erosion. Although marine flooding represents the primary risk at the second study site, coastal erosion will increase the risk of flooding of properties in the future due to the decrease in width of the protective coastal dunes. Comparison of our results with the coastal hazard maps published by the French government shows significant differences that can be explained by the fact that the risk of erosion was not considered in the Coastal Risk Protection Plans (PPRL) of the two municipalities considered in this study, which raises the question of the reliability of areas at risk defined without taking into account future shoreline evolution trends.